2013
DOI: 10.1371/journal.pone.0075133
|View full text |Cite
|
Sign up to set email alerts
|

Substance Use and Access to Health Care and Addiction Treatment among Homeless and Vulnerably Housed Persons in Three Canadian Cities

Abstract: IntroductionWe examined the prevalence of substance use disorders among homeless and vulnerably housed persons in three Canadian cities and its association with unmet health care needs and access to addiction treatment using baseline data from the Health and Housing in Transition Study.MethodsIn 2009, 1191 homeless and vulnerably housed persons were recruited in Vancouver, Toronto, and Ottawa, Canada. Interviewer administered questionnaires collected data on socio-demographics, housing history, chronic health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
50
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 41 publications
(50 reference statements)
3
50
0
1
Order By: Relevance
“…5--10 However, detailed data on SUD among homeless-experienced persons in primary care are lacking. One study of homeless patients at Federally Qualified Health Centers (FQHCs) reported dependence prevalence of 12-15% and binge drinking in 40%.…”
Section: Introductionmentioning
confidence: 99%
“…5--10 However, detailed data on SUD among homeless-experienced persons in primary care are lacking. One study of homeless patients at Federally Qualified Health Centers (FQHCs) reported dependence prevalence of 12-15% and binge drinking in 40%.…”
Section: Introductionmentioning
confidence: 99%
“…As might be expected, marginalized populations have been particularly affected by declining government expenditures on health care and physician shortages (Asanin & Wilson, 2008;Crooks, Agarwal, & Harrison, 2012;Khandor et al, 2011;Palepu et al, 2013). Furthermore, well publicized linkages between what are presented as "life-style choices" and illness position those who do not make "correct" choices as irresponsible citizens.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Homeless youth, similar to their adult counterparts, also tend to abuse substances at higher rates than their housed peers. [16][17][18] For example, one study of homeless youth concluded that about 75% of those surveyed met the clinical criteria for having a drug and/or alcohol use disorder. 19 According to other studies, 57%-70% of homeless youth reported recent use of alcohol, 20 57%-68% reported recent use of marijuana, 20 and 50% reported prescription drug misuse, 21 rates that are higher than those found in the general population.…”
mentioning
confidence: 99%